Medication adherence and health-related quality of life among patients with chronic obstructive pulmonary disease - Horvat Nejc; Locatelli Igor; Kos Mitja; Janežič Ana (Acta Pharmaceutica)
This study evaluated medication adherence and health-related quality of life (HRQoL) of Slovenian patients with chronic obstructive pulmonary disease (COPD) and examined the factors associated with HRQoL. Demographic and therapy information was collected from 65 patients through interviews. The St. George’s Respiratory Questionnaire and the Morisky Medication Adherence Scale were used to evaluate HRQoL and adherence, resp. A multiple linear regression model was used to assess the association between the factors and HRQoL. The mean St. George’s Respiratory Questionnaire score (range 0-100, with higher scores indicating lower HRQoL) was 41.4. COPD affected patients’ daily activities more than their social and psychological functioning. Slightly more than 53 % of the patients were optimally adherent, while 12 % were non-adherent. Patients with lower HRQoL had a larger number of medications for concomitant diseases, experienced COPD exacerbation in the last year, and had less education. No statistically significant correlation was found between medication adherence and HRQoL.